Behind the screens: telemediated work in the Canadian public sector. (1st July 2007) - Norene Pupo
Abstract : Among the recent measures undertaken in Canada to adapt the public sector to the 'new economy' in order to maintain or enhance economic competitiveness on an international level has been the adoption of new technologies and e-government, affecting both labour processes and service delivery. All three levels of government — municipal, provincial, and federal — have adopted 'virtual service techniques'. This paper examines telemediated processes and new work arrangements in the public sector and raises questions regarding the impact on workers and their trade unions, working conditions, service delivery, and social citizenship.